Factors influencing service performance of insurance agents - Rosnani, Mokhtar (2016)
The role of agents as intermediaries between customers and insurance company is important in the insurance industry. Insurance agents performance depends on the willingness of the agents to consult explain and convince potential customers about the proposed insurance policies either a conventional or Takaful systems or schemes. The purpose of this study is to investigate the factors that influenced the service performance of insurance agents A total number of 350 questionnaires were distributed to insurance agents in Northern Malaysia but only 291 were usable for analysis. Correlation and regression analysis were used to analyse all data. The findings indicated that agents’ service performance is positive related to all the four independent variables (commitment, motivation, attitudes and perceived behaviour control). In addition, from the multiple regression analysis that was conducted, it showed that agents’ attitude is the strongest factor influencing agents’ service performance.